2017
DOI: 10.1097/bot.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Randomized Control Trial Comparing a Novel Intramedullary Device (InterTAN) Versus Conventional Treatment (Sliding Hip Screw) of Geriatric Hip Fractures

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 48 publications
3
32
0
Order By: Relevance
“…CM nailing has proved especially popular for the treatment of unstable intertrochanteric and subtrochanteric hip fractures [ 35 ]. Indeed, patients experience an improved outcome when an intramedullary nail is used to treat their unstable intertrochanteric fracture [ 36 ]. CM nailing, compared with SHS, is associated with a shorter operating time, reduced intra-operative blood loss, and improved walking ability in unstable hip fractures [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…CM nailing has proved especially popular for the treatment of unstable intertrochanteric and subtrochanteric hip fractures [ 35 ]. Indeed, patients experience an improved outcome when an intramedullary nail is used to treat their unstable intertrochanteric fracture [ 36 ]. CM nailing, compared with SHS, is associated with a shorter operating time, reduced intra-operative blood loss, and improved walking ability in unstable hip fractures [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sub-group analysis showed that active and functional patients with unstable trochanteric fractures have better outcome regarding less shortening, better Functional Independence Measure (FIM) and Timed Up and Go test (TUG) after one year follow-up when the Trigen Intertan nail is used. 40 More prospective randomized comparative studies of recent dual lag screw systems with other fixation types are warranted to conclude what osteosynthesis is preferable in unstable trochanteric fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Human joint moment prediction is crucial to rehabilitation evaluation [1][2][3], athlete training evaluation [4][5][6], prosthesis and orthosis design [7][8][9], intramedullary device design [10][11][12] and human-robot interaction [13][14][15][16][17][18][19][20][21]. The precise prediction of joint moment can be fulfilled by the use of instrumented implants [22] which measures the relevant parameters of joint load in real time.…”
Section: Introductionmentioning
confidence: 99%